Using Visual Mapping to Promote Higher-Level Thinking in Music-Making - Groffman, Joshua; Wolfe, Zora M. (Music Educators Journal, 2019)
What tools are available to foster independent and critical thought in the music classroom? We propose that visual mapping—a method of representing relationships and associations between a main concept and other ideas, subtopics, or examples—is an ideal tool for doing exactly this. After examining the principles and usefulness of mapping in a variety of contexts, we discuss several specific ways in which mapping might be implemented in teaching music. We argue that the central strength of mapping is its ability to encourage users to be explicit and metacognitive about their knowledge. As such, it can be part of a constructivist stance whereby the instructor creates a student-centered classroom in which learners are active, engaged participants in their education.
Keywords: dept.mus; peer-reviewed